Tumor Decelerating and Chemo-Potentiating Action of Methyl Jasmonate on a T Cell Lymphoma In Vivo: Role of Altered Regulation of Metabolism, Cell Survival, Drug Resistance, and Intratumoral Blood Flow - Goel, Yugal; Yadav, Saveg; Pandey, Shrish Kumar; Temre, Mithlesh Kumar; Maurya, Babu Nandan; Verma, Ashish; Kumar, Ajay; Singh, Sukh Mahendra (Frontiers in Oncology, 2021)
Methyl jasmonate (MJ), a natural oxylipin, possesses a broad spectrum of antineoplastic potential in vitro. However, its tumor growth impeding and chemo-potentiating action has not been adequately investigated in vivo. Using a murine thymus-derived tumor named Dalton's Lymphoma (DL), in the present study, we examined if intratumoral administration of MJ can cause tumor growth impedance. We also explored the associated molecular mechanisms governing cell survival, carbohydrate & lipid metabolism, chemo-potentiation, and angiogenesis. MJ administration to tumor-transplanted mice caused deceleration of tumor growth accompanying prolonged survival of the tumor-bearing mice. MJ-dependent tumor growth retardation was associated with the declined blood supply in tumor milieu, cell cycle arrest, augmented induction of apoptosis and necrosis, deregulated glucose and lipid metabolism, enhanced membrane fragility of tumor cells, and altered cytokine repertoire in the tumor microenvironment. MJ administration modulated molecular network implicating Hsp70, Bcl-2, TERT, p53, Cyt c, BAX, GLUT-1, HK 2, LDH A, PDK-1, HIF-1α, ROS, MCT-1, FASN, ACSS2, SREBP1c, VEGF, cytokine repertoire, and MDR1, involved in the regulation of cell survival, carbohydrate and fatty acid metabolism, pH homeostasis, and drug resistance. Thus, the present study unveils novel molecular mechanisms of the tumor growth decelerating action of MJ. Besides, this preclinical study also establishes the adjunct therapeutic potential of MJ. Hence, the present investigation will help to design novel anti-cancer therapeutic regimens for the treatment of haematological malignancies.